SARANA DAN PRASARANA LEMPAR CAKRAM UNTUK MENDUKUNG PEMBELAJARAN MENDALAM - Andi Sri Rafiqa Hayu; Sri Defi; Jumarni; Iin Asriani; Martita Dewi; Veliska; Indra Fahmi; Asfar Makbul Khalifah; Mohd. Hisyamuddin; Kurniawan (STKIP Subang, 2026)
Facilities and infrastructure are important components in supporting the success of physical education learning, especially in discus throwing material. The availability of adequate facilities not only supports safety aspects but also increases the effectiveness of the learning process so that students are able to understand concepts, techniques, and practices in more depth. This article aims to analyze the role of discus throwing facilities and infrastructure in supporting the implementation of in-depth learning in Physical Education, Sports, and Health (PJOK) subjects. The method used is a literature study by reviewing various scientific sources, books, and regulations related to sports facility standards and in-depth learning approaches. The results of the study indicate that the presence of a standard field, discus with varying weights according to student levels, a safe landing area, training aids, and technology-based learning media contribute significantly to improving conceptual understanding, motor skills, critical thinking abilities, and student reflection. In addition, teachers have a strategic role in optimizing the use of facilities and infrastructure through active, collaborative, and student-centered learning. Thus, providing and managing adequate discus throwing facilities and infrastructure is a key factor in achieving effective, safe, meaningful, and in-depth learning that is oriented toward developing students' overall competencies.